Experiential Learning in the School of Leadership Model: Shaping Students’ Perceptions and Engagement - Lia Faramita (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to analyze the implementation strategy of the School of Leadership program and the internalization of leadership values among students at SMA IT Daarul Istiqlal. Student leadership is often reduced to formal organizational activities, thereby necessitating an in-depth examination of how leadership is developed through integrative learning experiences. This research employed a case study design with a qualitative-descriptive approach. Data were collected through semi-structured interviews with the principal, teachers, and students, as well as through in-depth observations. Data analysis was conducted systematically through the stages of data condensation, data presentation, and conclusion drawing. The findings reveal that the internalization of leadership values was carried out through three main pillars: integration into classroom learning activities through the experiential learning method, reinforcement through extracurricular activities, and the provision of dialogical spaces through school community communication forums (FKGM and FKWS). A strong organizational culture emerged as the primary supporting factor that transformed students’ motivation from external pressure into intrinsic needs. Despite challenges related to academic time management, the program successfully transformed students’ perceptions into those of change agents characterized by independence, empathy, and social responsibility. This study implies the importance of creating a dialogical school ecosystem to foster transformational leadership in a sustainable manner.